Reductive beta-scission of the hydroperoxides of fatty acids and xenobiotics: role of alcohol-inducible cytochrome P-450. - Vaz, A D (1990)
As shown previously in this laboratory, purified rabbit liver microsomal cytochrome P-450 form 2 (P-450 IIB4) catalyzes the reductive cleavage of hydroperoxides to yield hydrocarbons and either aldehydes or ketones. We have proposed that lipid hydroperoxides are the physiological substrates for the cleavage reaction and have shown that with 13-hydroperoxy-9,11-octadecadienoic acid the formation of pentane is roughly equimolar with respect to the NADPH consumed. In the present study, the other product was isolated and identified as 13-oxo-9,11-tridecadienoic acid. Of particular interest, the alcohol-inducible form of liver microsomal cytochrome P-450 form 3a (P-450 IIE1) is the most active of the isozymes examined in the reductive beta-scission of the 13-hydroperoxide derived from linoleic acid and the 15-hydroperoxide derived from arachidonic acid as well as the model compounds cumyl hydroperoxide (alpha, alpha-dimethylbenzyl hydroperoxide) and t-butyl hydroperoxide. In general, the forms of P-450 with lower activity, as judged by the rate of NADPH oxidation in the reconstituted system, give less of the cleavage products (hydrocarbon and oxo compound) and catalyze direct reduction of the hydroperoxides to the corresponding hydroxy compounds. The occurrence of the reductive cleavage reaction in liver microsomal membranes was demonstrated, and microsomes from animals treated with ethanol or acetone (P-450 IIE1 inducers) or phenobarbital (a P-450 IIB4 inducer) were more active than those from untreated animals. We suggest that the alcohol-inducible P-450, in addition to its known deleterious effects in chemical toxicity and chemical carcinogenesis, may enhance the reductive cleavage of lipid hydroperoxides with a resultant loss in membrane integrity.